(untitled) (Physical Education, Health and Social Sciences, 2025)
This study researches the impact of Financial Technology (FinTech) in the areas of banking transformation in Pakistan. It highlights particular adoption barriers such as regulatory restrictions, cybersecurity issues, trust deficits, and consumer apprehensions. The primary data was collected through the online survey distributed among respondents who are interested in FinTech across the country of Pakistan. A descriptive analysis alongside structural equation model (SEM) analysis was conducted for assessment of consumer adoption patterns and key determinants. Based on the facilitators, results suggest that 72% of the consumers are currently using the FinTech services. These results show increased usage, availability, and affordability. Risk of fraud and data compromise concerns, however, hinder adoption by a wider audience. Mainstream banks are also limited in their adoption of FinTech because of regulation and the technology resistance. There is progress However, Government initiatives like Raast (instant payment system) in Pakistan is boosting aid in financial access but there is still room for improvement. This study contributes to empirical knowledge in the FinTech exploring consumer behavior, challenges of regulation/law and future trends related to adoption in Pakistan. It provides strategic guidance for policy makers, investors, and banks in emerging markets.